1995
DOI: 10.1021/jf00058a011
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Some Insecticides from Vine to Wine

Abstract: The fate of residues of five insecticides (chlorpyrifos methyl, fenthion, methidathion, parathion methyl, and quinalphos) from the treatment on vine to the production of wine was studied. The influence of clarifying agents (bentonite, charcoal, potassium caseinate, gelatin, polyvinylpolypyrrolidone, and colloidal silicon dioxide) on residue concentrations in wine was also studied. The insecticide residues on grapes showed high decay rates after treatment, with first-order kinetics and half-lives ranging from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…k) Wine making : Frank et al (1990) observed a significant reduction in pesticide residues on fermentation of grapes into wine. During processing of grapes into wines, vinification with skins lead to a greater pesticide (86%) reduction than vinification without skins (50%) (Cabras et al 1991). The reduction in pesticide concentration was more evident with red wine verses the white wine vinfication process.…”
Section: Products Manufacturementioning
confidence: 94%
“…k) Wine making : Frank et al (1990) observed a significant reduction in pesticide residues on fermentation of grapes into wine. During processing of grapes into wines, vinification with skins lead to a greater pesticide (86%) reduction than vinification without skins (50%) (Cabras et al 1991). The reduction in pesticide concentration was more evident with red wine verses the white wine vinfication process.…”
Section: Products Manufacturementioning
confidence: 94%
“…The residues of fenhexamid in grapes decreased rapidly to one-third of the initial concentrations after almost one week after the application (Cabras et al, 2001). The decay rates of the organophosphorus insecticides are also very fast (Cabras et al, 1995). Navarro et al (2001) studied the disappearance of six pesticides (chlorpyrifos, fenarimol, metalaxyl, mancozeb, penconazole and vinclozolin), which are widely used in vineyards to control European grapevine moths (Eupoecilia ambiguella Hübn.…”
Section: Introductionmentioning
confidence: 99%
“…bentonite, potassium caseinate, gelatine-silicon dioxide and polyvinylpolypyrrolidone did not presented significantly decrease the pesticide residue concentration compared with non- clarified wine. On the other hand, clarification with charcoal significantly reduced (by 95%) tebufenozide residues in wine confirming that it is the most effective between other clarifying agents for reducing various pesticides in wine (Cabras et al 1995, Tsiropoulos et al 1999, Ruediger et al 2004, Fernandez et al 2005b, Oliva et al 2007). …”
Section: Field Sample Analysis and Wine-makingmentioning
confidence: 86%
“…Consequently, pesticides residues could also be present in wine if the effect of the wine-making technique on residue reduction is poor (Cus et al 2010, Cabras andConte 2001). Although data for fungicide residues on grapes and their fate during wine-making are widely available (Garcia-Cazorla and Xirau-Vayreda 1994, Cabras et al 1997, Cabras et al 1998, Garcia et al 1999, Cabras and Conte 2001, Fernandez et al 2005a, Mirlean et al 2005 Garau et al 2009), data for insecticide residues are quite limited (Cabras et al 1995, Sala et al 1996, Goodwin and Ahmad 1998, Navaro et al 1999 and even less as far as benzoulurea and other insect growth regulator insecticides are concerned (Tsiropoulos et al 1999). However, the type of wine-making process and the different oenological steps (with or without maceration, clarification, filtration) carried out can influence the reduction of pesticide residues (Fernandez et al 2005aand b, Oliva et al 2007, Cabras and Angioni 2000, Ruediger et al 2004).…”
Section: Introductionmentioning
confidence: 99%